International haemovigilance: what have we learned and what do we need to do next?. Issue 4 (6th February 2019) - Wood, E. M.; Ang, A. L.; Bisht, A.; Bolton‐Maggs, P. H.; Bokhorst, A. G.; Flesland, O.; Land, K.; Wiersum‐Osselton, J. C.; Schipperus, M. R.; Tiberghien, P.; Whitaker, B. I.
SUMMARY: The International Haemovigilance Network (IHN) defines haemovigilance as 'a set of surveillance procedures covering the whole transfusion chain (from the collection of blood and its components to the follow‐up of recipients), intended to collect and assess information on unexpected or undesirable effects resulting from the therapeutic use of labile blood products, and to prevent their occurrence or recurrence'. IHN, the International Society of Blood Transfusion and World Health Organization work together to support both developing and established haemovigilance systems. Haemovigilance systems provide valuable data on a range of adverse events related to blood donation and clinical transfusion, from donor syncopal events to transfusion‐transmitted infections, immunological complications and the impact of human errors. Harmonised definitions for most adverse reactions have been developed and validated internationally. Definitions of pulmonary complications are again under review. Haemovigilance data have resulted in changes in policy, products and practice, and can complement and inform clinical audit and research, leading to improved blood donor safety, optimised product use and better clinical outcomes after transfusion. However, more work is needed. Not all countries have haemovigilance systems in place. More robust data and careful analysis are required to improve the understanding of the causes, occurrence and clinical outcomes of these events. Wider dissemination of results will facilitate health policy development internationally, and implementation of haemovigilance recommendations will support further important progress in blood safety.